Haiti : Can Non-Public Schools Fill the Gap for Poor Children? - World Bank (World Bank, Washington, DC, 2015)
Worldwide, some 57 million primary school age children don't have the chance to go to school. Many factors hold these children back: poverty, poor health and overcrowded or faraway facilities. The problem is most acute in Sub-Saharan Africa, where some 30 million primary school age children aren't enrolled, but many countries in other regions are also still struggling to reach universal primary school enrollment. In some places, education experts and policymakers are looking to low-cost private schools- whether run by private providers, faith-bases groups or non-governmental organizations to educate more children, especially where the public system is unable to do so. In order to make private schools accessible, governments usually set a per student subsidy that is supposed to cover tuition. In turn, schools agree to charge fees to families. Development experts and policymakers have to consider numerous issues before implementing such approaches, from how to reach the target population to how to ensure schools maintain quality standards, among other things.